2019
DOI: 10.5137/1019-5149.jtn.26398-19.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of survival of patients with brain metastases according to prognostic indexes and treatment strategies

Abstract: AIM: To retrospectively evaluate the overall survival (OS) of patients with brain metastases (BMs) who had been treated with whole brain radiotherapy (WBRT) and Gamma Knife (GK) according to prognostic factors and prognostic index scores. MATERIAL and METHODS: The study included 91 patients with BMs who had been treated with WBRT and/or GK between 2014 and 2017. The patients with BMs were retrospectively evaluated regarding age, sex, Karnofsky Performance Status (KPS), recursive partitioning analysis (RPA) cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In addition, we found that the PIs in our study were not uniformly recommended in different studies, and there was a large discrepancy between the expected and actual survival[18, [40][41][42]. This nding supports the need for a better prognostic tool or index.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, we found that the PIs in our study were not uniformly recommended in different studies, and there was a large discrepancy between the expected and actual survival[18, [40][41][42]. This nding supports the need for a better prognostic tool or index.…”
Section: Discussionmentioning
confidence: 58%
“…Further, the dissimilar proportions of patients within the prognostic classes could be another reason. In addition, we found that the PIs in our study were not uniformly recommended in different studies, and there was a large discrepancy between the expected and actual survival [ 18 , 38 40 ].…”
Section: Discussionmentioning
confidence: 83%